2018
DOI: 10.29408/jel.v4i1.513
|View full text |Cite
|
Sign up to set email alerts
|

Identifikasi Kemampuan Berpikir Kritis Matematis Mahasiswa Berkemampuan Pemecahan Masalah Level Rendah dalam Pembelajaran Kalkulus Integral Berbasis Problem Based Learning

Abstract: AbstrakPenelitian ini bertujuan untuk mendeskripsikan profil kemampuan berpikir kritis mahasiswa berkemampuan pemecahan masalah level rendah dalam menyelesaikan soal integral Riemann yang disusun berdasarkan indikator kemampuan berpikir kritis matematis. Penelitian ini merupakan penelitian deskriptif kualitatif dengan subjek penelitian adalah mahasiswa kelas IIE tahun pelajaran 2016/2017 Program Studi Pendidikan Matematika FPMIPATI UPGRIS yang sedang mengikuti mata kuliah Kalkulus Integral. Teknik pengumpulan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The results of research conducted by Zetriuslita et al (2016) explained that students' critical thinking ability in solving integral calculus description problems, in identifying and giving reasons indicators is 7.69%, in generalizing 82.05%, and in analyzing and evaluate by 15.38%. Likewise, the results of research conducted by Nursyahidah and Albab (2018), which identified students' mathematical critical thinking ability in integral calculus; they found that there were students who were able to formulate problems correctly but incompletely; had not been able to determine the facts in the problem entirely and correctly; have not been able to use the correct evidence, have not been able to conclude according to facts; have not been able to act by providing further explanations; and have not been able to combine tendencies and abilities in making decisions. Similar results were obtained from the results of the calculus exam, which showed that students' mathematical critical thinking ability on the indicators (1) in data analysis, students who answered with problem analysis were 38.71%, (2) in assessing or evaluating the truth of arguments, students who answered by evaluating the truth of the argument as much as 12.90%, (3) in concluding and providing logical arguments from the results of the analysis, students who answered by concluding as much as 74.19%, and (4) in formulating problem-solving strategies, students who answered by showed ideas and strategies as much as 48.39%.…”
Section: Introductionmentioning
confidence: 98%
“…The results of research conducted by Zetriuslita et al (2016) explained that students' critical thinking ability in solving integral calculus description problems, in identifying and giving reasons indicators is 7.69%, in generalizing 82.05%, and in analyzing and evaluate by 15.38%. Likewise, the results of research conducted by Nursyahidah and Albab (2018), which identified students' mathematical critical thinking ability in integral calculus; they found that there were students who were able to formulate problems correctly but incompletely; had not been able to determine the facts in the problem entirely and correctly; have not been able to use the correct evidence, have not been able to conclude according to facts; have not been able to act by providing further explanations; and have not been able to combine tendencies and abilities in making decisions. Similar results were obtained from the results of the calculus exam, which showed that students' mathematical critical thinking ability on the indicators (1) in data analysis, students who answered with problem analysis were 38.71%, (2) in assessing or evaluating the truth of arguments, students who answered by evaluating the truth of the argument as much as 12.90%, (3) in concluding and providing logical arguments from the results of the analysis, students who answered by concluding as much as 74.19%, and (4) in formulating problem-solving strategies, students who answered by showed ideas and strategies as much as 48.39%.…”
Section: Introductionmentioning
confidence: 98%
“…Critical thinking is reasoning and deep awareness of what is received from different ideas, meaning that ideas and suggestions from someone about a phenomenon or event cannot be fully accepted if the concept does not run systematically and is a logical truth-seeking process (Nursyahidah & Albab, 2018). Critical thinking skills are very useful in everyday life (Salirawati et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a student-teacher candidate needs to have self-regulated learning (Kramarski & Michalsky, 2009;Paris & Winograd, 2003) so that one day they can become lifelong learner teachers. Self-regulated learning is one of the soft skills that need to be trained in students as agents of change related to the times every day (Karimpour et al, 2018;Nursyahidah & Albab, 2018). Bandura defines self-regulated learning as an individual's ability to monitor his behavior in learning and individual effort (Hargis, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Selfregulated learning is one of the soft skills students need. Nursyahidah & Albab (2018) stated that students are agents of change who need provision in the form of hard skills and soft skills in order to be able to participate in competition in a world that is constantly changing every day. Prospective teacher students need self-regulated learning and also need to foster it so that their enthusiasm for learning continues to be fostered.…”
Section: Introductionmentioning
confidence: 99%